Genomics and transcriptomics reveal new molecular mechanism of vibriosis resistance in fish - Zhou, Qian; Chen, Yadong; Chen, Zhangfan; Wang, Lei; Ma, Xinran; Wang, Jie; Zhang, Qihao; Chen, Songlin (Frontiers in Immunology, 2022)
Infectious diseases have caused dramatic production decline and economic loss for fish aquaculture. However, the poor understanding of fish disease resistance severely hampered disease prevention. Chinese tongue sole (Cynoglossus semilaevis) is an important economic flatfish suffering from vibriosis. Here we used genomic, transcriptomic and experimental approaches to investigate the molecular genetic mechanisms underlying fish vibriosis resistance. A genome-wide comparison revealed that the genes under selective sweeps were enriched for glycosaminoglycan (GAG) chondroitin sulfate (CS)/dermatan sulfate (DS) metabolism. Transcriptomic analyses prioritized synergic gene expression patterns in this pathway, which may lead to an increased CS/DS content in the resistant family. Further experimental evidence showed that carbohydrate sulfotransferases 12 (Chst12), a key enzyme for CS/DS biosynthesis, has a direct antibacterial activity. To the best of our knowledge, this is the first report that the chst12 gene has a bactericidal effect. In addition, CS/DS is a major component of the extracellular matrix (ECM) and the selection signatures and fine-tuned gene expressions of ECM-receptor interaction genes indicated a modification in the ECM structure with an enhancement of the barrier function. Furthermore, functional studies conducted on Col6a2, encoding a collagen gene which constitutes the ECM, pointed to that it may act as a cellular receptor for Vibrio pathogens, thus plays an important role for the Vibrio invasion. Taken together, these findings provide new insights into the molecular protective mechanism underlying vibriosis resistance in fish, which offers crucial genomic resources for the resistant germplasm breeding and infectious disease control in fish culturing.